Extreme Hydrological Events and Reservoir Methane Emissions - Sherman, Bradford S.; Ford, Phillip W. (Frontiers in Environmental Science, 2022)
Floating chamber measurements of CH4 and CO2 emissions from Cotter Reservoir (Canberra, Australia) were performed on five occasions between Oct 2010 and Apr 2012. The timing of the measurements spanned the first major flood events that followed drought-breaking rains that ended the Millenium Drought in southeast Australia. The flood events were the largest in 26 years and followed the 3 lowest flow years on record. The floods warmed the hypolimnion of this normally monomictic reservoir by 8 C during the first summer and by 3 C during the second summer of the study compared to 'normal' summer hypolimnion temperatures. In addition, the floods carried large amounts of vegetation and soil that had accumulated in the catchment during previous years. Average CH4 emissions prior to the flooding were low (4.3 mg-CH4 m-2 d-1) and relatively uniform across 8 measurement sites spaced along the long axis of the reservoir. Following the first floods, which occurred during spring and summer 2010-2011 and warmed the hypolimnion by 8 C, the mean reservoir CH4 emission increased to 99 mg-CH4 m-2 d-1 with emissions at the upstream end of the reservoir approximately 100 times greater than emissions near the dam wall. The following year (2011-2012) average emissions were lower (30 mg-CH4 m-2 d-1) and the longitudinal gradient weakened. A major flood occurred in autumn 2012 and warmed the hypolimnion by ~ 3 C, but emissions did not change much in response. We hypothesize that the changes in mean reservoir CH4 emission can be attributed to both thermal enhancement of sediment methanogenesis by a factor of 2-7, and to the supply of fresh organic matter from the catchment by a factor of 3.